2019
DOI: 10.1002/aoc.4891
|View full text |Cite
|
Sign up to set email alerts
|

Study of the effect of the ligand structure on the catalytic activity of Pd@ ligand decorated halloysite: Combination of experimental and computational studies

Abstract: Taking advantage of computational chemistry, the best diamine for the synthesis of a multi‐dentate ligand from the reaction with 3‐(trimethoxysilyl) propylisocyanate (TEPI) was selected. Actually, predictive Density Functional Theory (DFT) calculations provided the right diamino chain, i.e. ethylenediamine, capable to sequester a palladium atom, together with the relatively polar solvent toluene, and then undergo the experiments as a selective catalytic agent. The ligand was then prepared and applied for the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 60 publications
(72 reference statements)
2
20
0
Order By: Relevance
“…NCI plots computed by the NCIPLOT package, confirmed the significant additional non‐covalent interactions due to the aromatic rings of the IPr* ligand, whereas only the ones between the phenoxide and one of the aryl rings on the diphenylacetylene for the IMe based system (see Figure ). The plot for the IPr ligand is placed in between, and it confirms the effect of the substitution of phenyl by methyl groups, with much less favourable π‐π staking interactions . Thus, NCI plots and EDA analyses here unveil why the sterically more hindered IPr* ligand ends up showing less unfavourable kinetics and thermodynamics than expected for the C–O bond formation.…”
Section: Resultssupporting
confidence: 62%
“…NCI plots computed by the NCIPLOT package, confirmed the significant additional non‐covalent interactions due to the aromatic rings of the IPr* ligand, whereas only the ones between the phenoxide and one of the aryl rings on the diphenylacetylene for the IMe based system (see Figure ). The plot for the IPr ligand is placed in between, and it confirms the effect of the substitution of phenyl by methyl groups, with much less favourable π‐π staking interactions . Thus, NCI plots and EDA analyses here unveil why the sterically more hindered IPr* ligand ends up showing less unfavourable kinetics and thermodynamics than expected for the C–O bond formation.…”
Section: Resultssupporting
confidence: 62%
“…[21] In a recent study of palladium nanoparticles, highly active and selective hydrogenation of nitro group within nitroarenes was achieved using Pd@Hal/di-urea. [22] Functional groups possessing unsaturated bonds, such as esters, amides, and N=C-N bonds (ex: guanidine, which is known for Y-aromaticity [23] ), proved to be resilient to reduction. In addition, hydroxyl groups at positions other than benzyl remained, as shown in the reaction of 3-(pyridin-2-yl)prop-2-yn-1-ol, which could be quantitatively hydrogenated in this work, although we previously reported that use of 500 mol% Pd/C led to a moderate yield of 57 %.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, previous studies on dearomatic hydrogenation method of quinoline utilizing palladium nanoparticles reported selective hydrogenation on the ring containing nitrogen . In a recent study of palladium nanoparticles, highly active and selective hydrogenation of nitro group within nitroarenes was achieved using Pd@Hal/di‐urea . Functional groups possessing unsaturated bonds, such as esters, amides, and N=C‐N bonds (ex: guanidine, which is known for Y‐aromaticity), proved to be resilient to reduction.…”
Section: Resultsmentioning
confidence: 99%
“…[ 9–11 ] The increasing growth of Hal is due to its tunability and also capability to be incorporated in composites and hybrids. [ 12–15 ]…”
Section: Introductionmentioning
confidence: 99%
“…In the pursuit of our inquiries on the chemistry and usage of Hal, [ 14,32–37 ] herein, we wish to describe synthesis and application of a new magnetic composite of Hal and polymer for catalytic dye degradation. The target composite was covalent and fabricated through reaction of vinyl‐functionalized magnetic Hal with hydroxyethyl methacrylate (HEMA) and methacrylate polyhedral oligomeric silsesquioxane (POSS).…”
Section: Introductionmentioning
confidence: 99%